Case Report: A novel hemizygous missense PDHA1 variant in a Vietnamese boy with pyruvate dehydrogenase E1-alpha deficiency - Nguyen, Thi Thanh Ngan; Khanh, Nguyen Ngoc; Vu, Chi Dung; Nguyen, Ngoc-Lan; Tran, Van Khanh; Lien, Nguyen Thi Kim; Van Tung, Nguyen; Quan, Nguyen Duc; Hien, Nguyen Thanh; Giang, Tran Thi Huong; Xuan, Nguyen Thi; Tao, Nguyen Thien; et al. (Frontiers in Pediatrics, 2024)
A pyruvate dehydrogenase complex deficiency causes a reduction in adenosine triphosphate production and energy insufficiency, leading to neurological disorders. An abnormal E1-alpha protein originating from the PDHA1 gene with pathogenic variants is unable to communicate with E1-beta for the formation of the E1 enzyme, decreasing pyruvate dehydrogenase complex activity. In this study, we report a Vietnamese boy with lethargy, severe metabolic acidosis, increased serum lactate, hyperalaninemia, lactic acidosis, and globus pallidus lesions. Whole-exome sequencing and variant filtering identified a hemizygous missense variant NM000284.4 (PDHA1): c.479T>G (p.Phe160Cys) in the patient. The variant c.479T>G caused a single nucleotide substitution on exon 5 and was predicted to be a disease-causing variant in the in silico analyses. We present the first report with a genetic analysis of a Vietnamese patient with pyruvate dehydrogenase E1-alpha deficiency (PDHAD). Sanger sequencing demonstrated that the patient inherited the variant from his mother who harbored the variant in a heterozygous state, but no PDHAD symptoms were observed in her. In addition, a prenatal test of the patient's mother revealed a fetus with a normal genotype. Furthermore, the patient's father and sister both carried a normal allele. Based on the American College of Medical Genetics criteria, the variant c.479T>G was predicted to be a likely pathogenic variant. Using the combination of the patient’s genotype and phenotype, he was definitively diagnosed with pyruvate dehydrogenase E1-alpha deficiency. Our findings expand the mutational spectrum of neurological disorders and provide the scientific basis for genetic counseling for the patient's family.